OMNIMBUS LAW DAN PENYUSUNAN RENCANA TATA RUANG: KONSEPSI, PELAKSANAAN DAN PERMASALAHANNYA DI INDONESIA - Andi Setyo Pambudi; Santun R.P. Sitorus (Jurnal Ilmiah Wahana Bhakti Praja, 2021)
The phenomenon of development problems is related to spatial planning and development planning. Ideally, spatial planning and development must be finished in an integrated manner, both in substance, spatially, and in terms of funding. Conceptually, the preparation of spatial plans is related to spatial-geographical expressions that include economic, social, environmental, and cultural policies of societies. Spatial planning is related to regional development in which there are sectors with the distribution of resources and all activities and problems in various types and scales. This paper attempts to explain the preparation of spatial plans, both in terms of conception, implementation, and the problems faced, including presenting problems that occur at the current site level. The method used is an information based on literature review from regulations, journals, books, and other relevant sources. The results of the analysis showed that spatial planning is facing the challenges of COVID-19 and the implementation of the Omnimbus Law and its derivatives. The strong aspect of "utilization” of space in the latest regulations related to spatial planning which is influenced by the Omnimbus Law indicates that spatial control is a challenge for planners.